Principle and prudence in Western political thought - Lynch, Christopher, 1963-; Marks, Jonathan, 1969- (Albany : State University of New York Press, 2016)
Discussions of the place of moral principle in political practice are haunted by the abstract and misleading distinction between realism and its various principled or "idealist" alternatives. This volume argues that such discussions must be recast in terms of the relationship between principle and prudence: as Nathan Tarcov maintains, that relationship is "not dichotomous but complementary." In a substantive introduction, the editors investigate Leo Strauss's attack on contemporary political thought for its failure to account for both principle and prudence in politics. Leading commentators then reflect on principle and prudence in the writings of great thinkers such as Homer, Machiavelli, and Hegel, and in the thoughts and actions of great statesmen such as Pericles, Jefferson, and Lincoln. In a concluding section, contributors reassess Strauss's own approach to principle and prudence in the history of political philosophy.
Machiavelli and Homer on the man and the beast / Peter J. Ahrensdorf -- Practice and principles in ancient statesmanship / Richard S. Ruderman -- Weaponizing words : some pathologies of strategic communication in Thucydides' Peloponnesian War / Karl Walling -- "And God led them not by the way of the Philistines" : principles, practice, and prudence in the Torah -- Hillel Fradkin -- The wedding of Logos and Ergon : Josephus's defense of the Torah in Against Apion / Clifford Orwin -- Machiavelli's literary self-portraits : Clizia, the Discourses, alternating epochs, and the pursuit of fame / Vickie Sullivan -- Principle and practice in Locke's Some thoughts concerning education / Jonathan Marks -- Montesquieu's Legislator : putting order in the laws / Diana J. Schaub -- On the Lawgiver : Rousseau's articulation of the political problem / Heinrich Meier -- David Hume on principle, nature, and the indirect influence of philosophy / Richard Velkley -- Principle and practice in Hegel's critique of Rousseau / Paul Franco -- Principle and prudence : the use of force from the founders' perspective / Nathan Tarcov -- Jefferson's "Summary view" reviewed, yet again / Ralph Lerner -- Lincoln's Enlightenment / Steven B. Smith -- Strauss on the theoretical and practical origins of philosophy / Svetozar Minkov -- The prudence of philosophic politics : Leo Strauss's "Introduction" to Thoughts on Machiavelli / Christopher Lynch -- Strauss's second statement on locke / Nasser Behnegar -- Leo Strauss's Nietzsche / Robert B. Pippin.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Political science -- Philosophy; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Political science -- Philosophy